The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0959354315585661
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking situated and embodied social psychology

Abstract: This article aims to explore the scope of a Situated and Embodied Social Psychology (ESP). At first sight, social cognition seems embodied cognition par excellence. Social cognition is first and foremost a supraindividual, interactive, and dynamic process (Semin & Smith, 2013). Radical approaches in Situated/ Embodied Cognitive Science (Enactivism) claim that social cognition consists in an emergent pattern of interaction between a continuously coupled organism and the (social) environment; it rejects represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…Despite growing recognition in our field that psychological processes are closely tied to physical, bodily processes (Niedenthal et al, 2005;Pouw & Looren de Jong, 2015;Schubert & Semin, 2009; E. R. Smith & Semin, 2004), a fully embodied account must also acknowledge that any given behavior also depends on the supporting structure of the physical environment. Walking, for example, is a behavior that not only requires certain bodily functioning and neural capacities, but it also requires complementary environmental properties, such as a level surface, a lack of obstacles, and an adequate gravitational field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite growing recognition in our field that psychological processes are closely tied to physical, bodily processes (Niedenthal et al, 2005;Pouw & Looren de Jong, 2015;Schubert & Semin, 2009; E. R. Smith & Semin, 2004), a fully embodied account must also acknowledge that any given behavior also depends on the supporting structure of the physical environment. Walking, for example, is a behavior that not only requires certain bodily functioning and neural capacities, but it also requires complementary environmental properties, such as a level surface, a lack of obstacles, and an adequate gravitational field.…”
Section: Resultsmentioning
confidence: 99%
“…First, over the last two decades, a substantial body of research has demonstrated the embodied and situated nature of cognitive processes (Barsalou, 1999(Barsalou, , 2008Marsh, Johnston, Richardson, & Schmidt, 2009;Niedenthal, Barsalou, Winkielman, Krauth-Gruber, & Ric, 2005;Schubert & Semin, 2009; E. R. Smith & Semin, 2004). Perspectives on the specifics of what embodiment entails vary (Alessandroni, 2018;Pouw & Looren de Jong, 2015), but they are consistent in their critiques of the traditional cognitivist framework conceptualizing the mind as an isolated information processor. Instead, one's physical, bodily state is seen as playing a central role in mental activity, implying that psychological activity must be explained not just in terms of representations and mental models but also in terms of the actions of the entire physical organism.…”
mentioning
confidence: 99%
“…One of the key principles emerging from recent work in embodied psychology is the recognition that cognitive processes emerged specifically to facilitate adaptive behaviour in the physical world (Cole & Balcetis, ; Smith & Semin, ; Wilson, ). A comprehensive embodied and situated perspective on human social functioning therefore requires addressing the relation between an actor and the objects and environment with which he or she seeks to act (Marsh, Johnston, Richardson, & Schmidt, ; Pouw & Looren de Jong, ). The current studies provide evidence that the social meaning and the functional meaning of physical objects are inextricably intertwined for human perceivers.…”
Section: Resultsmentioning
confidence: 99%
“…So an increasing number of brain imaging studies are confirming an embodied view of IWMs (Bretherton & Munholland, 2016). So viewing IWMs as embodied simulations is not only fully in the 'spirit' of Bowlby's original conception for IWMs, but also matches the 'word' of what he wrote about IWMs when he first introduced them (Pouw & de Jong, 2015).…”
Section: From Internal Working Models To Embodied Working Modelsmentioning
confidence: 62%
“…But as we saw in section 5.1 the predictive processing framework (Clark, 2014) provides a strong alternative to sensorimotor enactivism, and it is also an alternative to the adaptive control of basic minds presented in this section that would support close interaction between lower level control mechanisms and higher level linguistic mediation. So future work can more closely examine whether Attachment Theory is best revised within a 'representation friendly' framework (Pouw & de Jong, 2015) or the more radical approach of basic REC minds (Hutto & Myin, 2013).…”
Section: A Radical Enactivist Manifesto For Attachment Theory?mentioning
confidence: 99%